Attraction induced frictionless sliding of rare gas monolayer on metallic surfaces: an efficient strategy for superlubricity. Issue 18 (11th April 2017) - Sun, Junhui; Zhang, Yanning; Lu, Zhibin; Xue, Qunji; Wang, Liping
Abstract : Interfacial attraction-induced frictionless sliding of rare gas monolayers on metal substrates. Abstract : Friction on a nanoscale revealed rich load-dependent behavior, which departs strongly from the long-standing Amonton's law. Whilst electrostatic repulsion-induced friction collapse for rare gas sliding over metallic surfaces in a high-load regime was reported by Righi et al. ( Phys. Rev. Lett., 2007, 99, 176101), the significant role of attraction on frictional properties has not been reported to date. In this study, the frictional motion of Xe/Cu(111), Xe/Pd(111) and Ar/Cu(111) was studied using van der Waals corrected density functional calculations. An attraction-induced zero friction, which is a signal of superlubricity, was found for the sliding systems. The superlubric state results from the disappearance of the potential corrugation along the favored sliding path as a consequence of the potential crossing in the attractive regime when the interfacial pressure approaches a critical-value. The finding of an attraction-driven friction drop, together with the repulsion-induced collapse in the high-load regime, which breaks down the classic Amonton's law, provides a distinct approach for the realization of inherent superlubricity in some adsorbate/substrate interfaces.